Island residents' identities and their support for tourism: An integration of two theories - Nunkoo, R.; Gursoy, D; Juwaheer, T. (Routledge, 2010)
Most studies that examine tourism impacts and community attitudes have been carried out from the perspective of industrialized economies, making the findings less valid for small islands. This paper discusses some pertinent issues in relation to tourism develop- ment and community attitudes in small islands, and it develops and presents a conceptual framework based on social exchange theory and identity theory. The different facets of identity relevant to small-island communities that are likely to influence attitudes and support for tourism are incorporated in the framework and discussed. These include occupational identity, environmental identity and gender identity. Based on these, five propositions are developed. The study concludes that inclusion of identity variables in behavioral models could increase their predictive power in explaining attitudes to tourism and consequent support for the industry. © 2010 Taylor & Francis.